Reading for Three Criticism Works, in Farhang Weekly journal, in the Viewpoints of Critical Theory of Criticism - Karwan Idrees Majeed; Karzan Mohsen Qadir (Zanco Journal of Humanity Sciences)
The study is entitled ‘’Reading for Three Criticism Works, in Farhang Weekly journal, in the Viewpoints of Critical Theory of Criticism’’, it consists of the introduction and two sections: section one is theoretical background, it includes five topics of critical theory of criticism, the first is about the theory itself, the second is about the terminologies of the theory, the third is about the objectives of the theory, the fourth is the role and importance of the critical theory of criticism in enhancing the text and literary criticism, the fifth is about the history of rising of critical theory of criticism in literary criticism in the West, Arab and Kurdish literature. While the second section is practical, it is the implementation of some Kurdish Examples in the Farhang Weekly Journal, which is an intellectual Critical journal.   Then, the most important concluding points are displayed. The references are adequately ordered. Finally, the abstracts in Arabic and English are provided.